Interfaces entre o ensino médio regular e a juvenilização na EJA: diálogos, entrelaçamentos, desafios e possibilidades sobre quefazeres docentes - Freitas, Larissa Martins (2015)
This Master's Thesis is part of the Training Research Field, Knowledge and Professional Development of the Postgraduate Program in Education of the Federal University of Santa Maria/RS. We aim, with this research, understand how the educators (teachers) express the words about his teaching whatdoings through Dialogical Circles Investigative-training, considering the interfaces between High School and the youthnization in Youth and Adult Education (EJA), in view of a humanizing educational praxis. Therefore, we seek to answer the following research problem: how, through the Dialogical Circles Investigative-training, educators announce their teaching whatdoings reflecting on the interfaces between regular school and the youthnization in EJA, in view of educational praxis humanizing? Methodologically this study is based on a qualitative approach of the study case type (multicases), but also has research training features, as coauthors subjects actively participate in all stages of research. For the dynamics of formation meetings with educators, we use the methodology of the Dialogical Circles Investigative-training, inspired by Freire's Culture Circles in approach to research-training (JOSSO, 2004, 2010). As theoretical and conceptual contributions we used Paulo Freire's propositions in dialogue with other authors such as: Charlot (2000), Brandão (2013), Henz (2010, 2012), Arroyo (2001), Carrano (2011), Imbernón (2009, 2010, 2011), Garcia (2010), among others. Five (5) thematic generating analysis and understanding emerged from the dialogues with educators and students: the processes of auto(trans)formation of the educator; the teaching content and/or learning; the youthnization process in EJA; the learning and unlearning: frustrations and hopes and the challenge of dialog of loveliness and rigor. For analysis and interpretation of results, we use the focus on hermeneutic approach, as it allows to understand the reality that appears from the way in which each is in the world. Listening to students and, from their speeches, talking with educators, we found that the students who seek EJA are mainly young people between 18 (eighteen) and 21 (twenty-one) years, who migrated to the modality because they have experienced unsuccessful experiences in the regular High School and / or due to lack of meaning given for them to said step, and also seeking a more humane, meaningful and loving education. We noted that in EJA, teachers have a different look for young students and are committed to reflect on their teaching whatdoings in order to better accommodate these students and make teaching in the modality an effectively mobilizing significant and learning mobilizing, though they still have resistance to dialogue about their whatdoings in regular education. We concluded that there are many challenges facing the permanent auto(trans)formation of high school educators, in order to provide an awareness-and liberating education that enables them to be both teachers themselves as students, as well as realize that EJA has sought to move in this direction.